Model Dinamika Sosio Ekonomi Ibnu Khaldun: Korupsi sebagai Determinan Kemiskinan di Pulau Jawa - Siti Nur Latifah (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2025)
In Islamic history, one of the scholars who discussed the problem of poverty was Ibnu Khaldun. In his analysis, the phenomenon of the rise and fall of a civilization is not only caused by economic variables, but also by a number of non-economic factors. Therefore, in his book entitled